An assessment of poor governance as a challenge affecting service delivery in local authorities: a case study of Zvishavane town council, 2013-2016 - Tambura, Chiedza (Midlands State University, 2017)
The study is an assessment of poor governance and service delivery in Zimbabwean Urban local authorities using Zvishavane Town Council as a case study. It focuses at the issue of poor governance and how it affects service delivery. The research hypotheses of the study postulate that due to poor governance in local authorities the effective and efficient delivery of service is being compromised. The major research objectives of this study were to examine the issue of poor governance as a challenge affecting service delivery at Zvishavane Town council, to examine the causes of poor governance and to outline the services that Zvishavane Town council is failing to deliver among others. Zvishavane Town council is the closest tier of government which deals with the people at grassroots levels and it acts as a helping hand to the central government. During the research different data collection methods were used which were questionnaires, key informant interviews and documentary interviews as well as direct observations. During the course of the research the causes of poor governance were established which are corruption, economic instability as well as political interference among others. Local authorities are failing to deliver services such as water, health, solid waste management, street lighting and refuse collection, sanitation and hygiene and road maintenances. The recommendations were also made to ZTC which are citizen involvement in decision making as well as governance issues, engage in partnerships with big companies and embark on income generating projects in order to have a broad revenue base. Therefore the study will focus on the issue of poor governance and how it affects effective service delivery.